2005
DOI: 10.1021/jp046032g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Silver Nanoparticles Supported on Silica Spheres

Abstract: In this work, we investigate the catalytic properties of silver nanoparticles supported on silica spheres. The technique to support silver particles on silica spheres effectively avoids flocculation of nanosized colloidal metal particles during a catalytic process in the solution, which allows one to carry out the successful catalytic reduction of dyes. The effects of electrolytes and surfactants on the catalytic properties of silver particles on silica have been investigated. It is found that the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
422
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 689 publications
(453 citation statements)
references
References 52 publications
8
422
0
4
Order By: Relevance
“…Ag, Pt, Au and Pd), silver (Ag) is the metal of abundance for prospective applications in the field of biological systems, living organisms and medicine. Due to their elite properties, AgNPs appear to have quite a lot of applications, such as catalysts in chemical reactions [14,15] , electrical batteries and in spectrally discriminative coatings for absorption of solar energy [16,17] as optical elements, pharmaceutics and in chemical sensing and biosensing [18][19][20] .…”
Section: Research Papermentioning
confidence: 99%
“…Ag, Pt, Au and Pd), silver (Ag) is the metal of abundance for prospective applications in the field of biological systems, living organisms and medicine. Due to their elite properties, AgNPs appear to have quite a lot of applications, such as catalysts in chemical reactions [14,15] , electrical batteries and in spectrally discriminative coatings for absorption of solar energy [16,17] as optical elements, pharmaceutics and in chemical sensing and biosensing [18][19][20] .…”
Section: Research Papermentioning
confidence: 99%
“…It is also known to catalyse reactions involving the oxidation of ethylene and methanol. [26,27] Silver oxide nanoparticles exhibit good fluorescence [4] and optical properties, [5] and have the potential to be used in data storage devices of the future. Their property of optical fluorescence memory facilitates their usage in optical media to enhance the readout signal by efficient utilisation of laser energy.…”
mentioning
confidence: 99%
“…Previous studies have also demonstrated their potential applications in LC as mentioned above. Recently, synthesis of nanometer-sized core-shell structures consisting of silica core and precious metal shell (e. g., Au, Pt, Ag) as well as precious metal core and silica shell has become an increasingly important topic [53][54][55][56][57][58][59][60][61]. The precious metal nanoparticles are of several nanometers in diameter in the resulting core-shell composites of several hundred nanometers in size.…”
Section: Future Possibilities For Nanomaterialbased Stationary Phasesmentioning
confidence: 99%